Sociologia no ensino médio brasileiro : a importância de no mínimo duas aulas semanais - Pereira, Alysson Cipriano (2023)
The study aims to discuss public policies for basic education that affect the discipline of Sociology, seeking to understand the current educational legislation in the country, understanding its advances and setbacks in the course of history. Why did Brazilian states implement Sociology classes in high school with one or two classes per week? Why did this implantation not occur in a systemic way? Does the political situation reflect on the decision-making of our elected representatives who approved the current National Common Curricular Base (BNCC/2018) for High School? What will be the pedagogical possibilities of Sociology teachers in high school in the State of Mato Grosso after the implementation of the new BNCC? How much time will be devoted to teaching this subject in the new BNCC? Will it be the same between the states of the Brazilian federation? These issues will be addressed in this master's thesis in Sociology, emphasizing the importance of pedagogical time for the teaching relationship. It is necessary to understand the process of the return of Sociology to High School and, unfortunately, the frustrations and anxieties experienced by the teachers of this discipline due to the constant threats to withdraw or reduce classes. What are the impacts of the BNCC approved for the discipline of Sociology? Will it cause quality losses for teachers and students? Will it harm the formation of the youth of our society as a whole? In order to try to answer these questions, a quantitative and qualitative research was carried out with teachers from Maringá (PR) and Rondonópolis (MT) because they had different working and teaching conditions before and after the implementation of the BNCC in 2022. A semi-structured interview was also carried out with a union representative from each state, namely, SINTEP-MT and APP-Syndicate, for representing the labor rights of professionals in this discipline in High School. In the understanding that laws are not natural, but socially constructed, aligning the historical knowledge of Sociology, which has always been on the sidelines in the Brazilian educational system, allows the fundamental theoretical-scientific preparation to remain mobilized, avoiding new retaliations to this in the student environment. This master's thesis wants to address the possibility of standardizing two classes per week of the discipline in the part destined for Basic General Training of the current BNCC, whether in Mato Grosso, Paraná or throughout Brazil.